Incalculable Harm: Analyzing the Impact of the COVID-19 Pandemic on Immigration Detention in Canada - Arbel, Efrat; Joeck, Molly (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
This paper reflects on the impact of the COVID‑19 pandemic on immigration detention in Canada. Drawing on research spanning 2020 to 2022, we analyze how the pandemic impacted rates of detention, conditions of detention, and other related issues. Data released by the Canada Border Services Agency shows that despite an initial decrease in absolute numbers, Canada detained people at a higher rate after the onset of the pandemic than it did prior. Canada also held people for longer periods of time and relied more heavily on jails than dedicated Immigration Holding Centres. Conditions of confinement deteriorated significantly across all detention facilities, but most acutely in jails. The abrupt shift towards conducting detention review hearings exclusively by remote means, and initially only by telephone—without ensuring meaningful contact between detainees and their counsel—further impeded detainees’ ability to understand and participate in their own hearings. These factors, combined with increased isolation within jails and detention facilities, increased use of segregation, diminished availability of alternatives to detention, the continued detention of children and separation of families, and the persistence of structural racism and disregard for detainee mental health paint a very grim picture. This research drives us towards the conclusion that the COVID‑19 pandemic has had a devastating impact on immigration detention in Canada. Rather than drive the immigration detention regime towards greater rates of release, as early researchers hoped, the pandemic ushered in an increased reliance on detention under worse conditions, as well as greater alienation, degradation, and dehumanization of detainees. We conclude our analysis by identifying key criteria that must be prioritized to avoid further entrenching the worst of the COVID‑19 era practices and call for the gradual abolition of immigration detention in Canada.